Drought tolerance in upland rice: identification of genotypes and agronomic characteristics - Cleber Morais Guimarães; Adriano Pereira de Castro; Luís Fernando Stone; Jaison Pereira de Oliveira (Acta Scientiarum. Agronomy, 2016)
This study aimed to identify upland rice cultivars and elite lines that are tolerant to drought and the agronomic traits associated with this tolerance. Forty-one genotypes were evaluated in a randomized block design with three replications in experiments with and without water stress at the Experimental Station of Emater, in Porangatu, Goiás State, in 2011 and 2012. The first experiment was well-irrigated throughout plant development and the second experiment was irrigated only up to 40 days after emergence, after which water stress was imposed. A multivariate analysis using Ward’s method was applied, and the genotypes with and without water stress were classified into six and seven clusters, respectively, based on the average yield in the two years of experimentation. The most productive cluster under water stress comprised the genotypes AB062041, Douradão, Guarani, BRS Aimoré, and Tangará. The first four genotypes of this cluster were also ranked in the second most productive cluster under  well-irrigated conditions. In the selection for drought tolerance, the genotypes that exhibit precocity, less dense panicles, low sterility and greater 100-grain weight under water stress should be prioritized.